Physical and Mental Workload Measurement at the Sterilizer Station Using HRR and DRAWS at Cot Girek Palm Oil Mill - Rendy Purba; Cut Ita Erliana; Amri (SEULANGA SYSTEM PUBLISHER, 2026)
Physical and mental workload are important factors affecting workers' performance. Excessive workload may cause fatigue, reduce concentration, and increase the risk of work-related errors. Therefore, workload assessment is necessary to determine workers' workload levels and provide appropriate improvement recommendations. PT Perkebunan Nusantara IV Regional VI Unit PKS Cot Girek is a palm oil mill that produces crude palm oil (CPO). The sterilizer station is one of the critical workstations where workers push lorries, pull wire ropes, manually open and close sterilizer doors, and monitor the sterilization process. This study aimed to measure physical workload using the Heart Rate Reserve (HRR) method, assess mental workload using the Defence Research Agency Workload Scale (DRAWS) method, and propose improvement recommendations. The results showed that the physical workload required improvement, with %HRR values of 40.48%, 30.98%, and 31.17% for Workers 1, 2, and 3, respectively. Mental workload was classified as overload, with DRAWS scores of 67.85%, 64.70%, and 63.45%, respectively. Improvement recommendations include increasing the number of workers, improving the sterilizer door mechanism, maintaining the capstan, repairing the lorry rail track, implementing job rotation, clarifying task allocation, providing operational training, and improving the lorry positioning system to enhance safety, productivity, and work efficiency.